Clinical cardiovascular pharmacology in anesthesiology - Pharmacology of myocardial protection - Part 2 - Amaral, Cristina (Journal of the Portuguese Society of Anesthesiology, 2016)
An increasingly older population in developed countries originated a high prevalence of patients taking cardiovascular medication. Anesthesiologists must know indications and therapeutic interactions between this drugs and anesthetic agents. Available evidence let’s talk about the pharmacology of myocardial protection. The current guidelines seem to follow positive outcome studies concerning what drugs should be introduced, continued or suspended throughout the perioperative period.